1982
DOI: 10.1128/iai.35.2.702-708.1982
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxins produced by vibrio fluvialis

Abstract: The results of studies with cell-free extracts and culture supernatant fluids of Vibrio fluvialis (a recently recognized, potential enteric pathogen for humans) grown in the absence and presence of lincomycin indicated that the bacterium could produce (i) a factor which causes CHO cell elongation (CEF) similar to that elicited by V. cholerae enterotoxin and by the heat-labile enterotoxin of Escherichia coli, (ii) cytolysin(s) active against erythrocytes, (iii) nonhemolytic, CHO cell-killing factor(s), and (iv)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 18 publications
1
20
1
1
Order By: Relevance
“…The toxin has hemolytic and proteolytic activities and the molecular weight is about 135,000. The results of the present study showed that the toxic substance of V. anguillarum differs from the toxins of V. vulnificus (9) and V. fluvialis (10). The toxic substance of V. anguillarum has no hemolytic nor protease activity.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The toxin has hemolytic and proteolytic activities and the molecular weight is about 135,000. The results of the present study showed that the toxic substance of V. anguillarum differs from the toxins of V. vulnificus (9) and V. fluvialis (10). The toxic substance of V. anguillarum has no hemolytic nor protease activity.…”
Section: Discussioncontrasting
confidence: 48%
“…The toxin of V. vulnificus is thermolabile and has cytolytic and hemolytic activities, and causes vascular permeability. Extracellular toxin was also demonstrated in the culture supernatant fluid of V. fluvialis (10). The toxin has hemolytic and proteolytic activities and the molecular weight is about 135,000.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mechanism of gastroenteritis due to this vibrio is not totally explained. Some toxins responsible for fluid accumulation in the rabbit ileal loop and in suckling mice have been reported (West 1989); other authors reported the presence of cytolysins, and a similar effect in Chinese hamster ovary (CHO) cells reported as the LT toxin from E. coli (Lockwood et al 1982). The high frequency of positive results in the Dean test (40.3%), the RIL test (49.3%) and also in some cases, the haemorrhagic fluid found in rabbit ileal loop in tests of strains of V. Jlzlvialis isolated in this study, was probably due to cytolysins or haemolysins.…”
Section: Discussionmentioning
confidence: 92%
“…Damselysin, a phospholipase D, has been purified, and many of its biological and physicochemical properties have been characterized (10,12,13). Many Vibrio species are known to produce cytolysins (9,14,19,23,(26)(27)(28) whose roles in the pathogenesis of diseases caused by the bacteria need to be determined. In that regard, cytolysins are known to be virulence factors for Aeromonas hydrophila, Listeria monocytogenes, and some Escherichia coli strains (3).…”
mentioning
confidence: 99%